CHARACTERIZATION OF BIOSURFACTANT PRODUCING MICROORGANISMS FROM OIL CONTAMINATED SOIL - R. UDAYASREE,; V.V.LAKSHMI, (International Journal of Pharma and Bio Sciences, 2015)
Biosurfactants are surface active compounds released by various microorganisms. These are amphipathic molecules with both hydrophilic and hydrophobic moieties that partition preferentially at the interface between fluid phases. Biosurfactants have a wide variety of applications in the petroleum, food and pharmaceutical industries as emulsifiers and wetting agents. They also help in clearing petroleum spills and reducing environmental pollution. Bacillus sp. showing efficient degradation of hydrocarbons was isolated and characterized. High emulsification activity was observed on a wide range of hydrocarbons and oils in 24hrs the highest being more than >88% emulsification index( EI 24 ) with Coconut oil, Xylene, Olive oil Engine oil, and Kerosene with BS2. The activity was associated with the production of high molecular weight bioemulsifier with potential applications.